Understanding the Polish capital market : from emerging to developed - Dietl, Marek; Zarzecki, Dariusz (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The Polish capital market has been developing successfully over the last four decades. The Warsaw Stock Exchange (GPW) was recognized by FTSE Russell as an emerging market in 2004, and in 2018, it was one of the 25 most developed markets in the World. The upgrade of Poland to developed market status represents an acknowledgement of the progress of the Polish economy and capital markets and is a major step in their development. The GPW uses a state-of-the-art trading system and its listed companies meet the highest standards of corporate governance and disclosure requirements. This book is authored by the most renowned Polish scholars. Contributions cover a broad range of topics including the links between monetary policy and capital market performance, micro- and macro- market structure and investors and issuers' behavior strategies. All of the chapters are rooted in modern economic and finance theory and all have an empirical component based on the most recent data, and in some cases including the Covid-19 impact on the capital markets. The book provides a comprehensive approach to theory and modeling combined with state-of-the-art methodology. The book is addressed primarily to academics and practitioners dealing with capital markets. It will be of particular interest to researchers studying the transformation of emerging markets that are steadily maturing towards developed market status. The book is a useful guide for doctoral and master's students in economics, finance and capital markets"--
Keywords: Capital market -- Poland; Finance -- Poland; BUSINESS & ECONOMICS / Investments & Securities; BUSINESS & ECONOMICS / Banks & Banking; BUSINESS & ECONOMICS / Corporate Finance